Expression and clinical significance of WWOX, Elf5, Snail1 and EMT related factors in epithelial ovarian cancer - Hu, Yakun (Oncol Lett, 2020)
Expression and clinical significance of WW domain-containing oxidoreductase (WWOX), Elf5, Snail1 and epithelial-mesenchymal transition (EMT) related factors in epithelial ovarian cancer were investigated. Ovarian cancer tissues of 300 epithelial ovarian cancer patients and the adjacent normal tissues were analyzed. Immunohistochemical method was used to detect the expressions of WWOX, Elf5, Snail1 and EMT marker molecules in the specimens. The relationship between the indicators and clinicopathological parameters, and prognosis of patients with ovarian cancer was analyzed. The relationship between WWOX, Elf5, Snail1 and EMT marker molecules E-cadherin, N-cadherin and vimentin in ovarian cancer tissues was analyzed. The expression levels of WWOX, Elf5, Snail1 and EMT marker molecules in epithelial ovarian cancer tissues were significantly different from those in adjacent normal tissues, and were related to surgical pathological stage, pathological grade and lymph node metastasis. High expressions of WWOX and Elf5 were related to the survival rate of patients. The survival rate of patients with positive expression was significantly higher than that of negative expression. FIGO stage, pathological grade, lymph node metastasis and expression of WWOX and Elf5 were all independent factors affecting postoperative prognosis in ovarian cancer patients. In conclusion, the expression levels of WWOX, Elf5, Snail1 and EMT related factors in epithelial ovarian cancer tissues are consistent and different. The expression levels of WWOX and Elf5 are related to the survival and prognosis of patients with epithelial ovarian cancer.